2019
DOI: 10.1016/j.envres.2018.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Vegetables cultivated with exposure to pure and naturally occurring β-N-methylamino-L-alanine (BMAA) via irrigation

Abstract: Bioaccumulation and biomagnification of β-N-methylamino-L-alanine (BMAA), a potent neurotoxin, has been demonstrated in various food webs. It is alarming as this intensification of BMAA will result in exposure to higher concentrations from a direct cyanobacterial source. As more food items are being identified as a source of BMAA and with the large variations in BMAA content, the aim of the present study was to evaluate BMAA uptake by, and accumulation in, two commonly consumed vegetables, Lactuca sativa and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Irrigation with polluted water is the primary route of introduction of cyanotoxins (microcystins) in agricultural soils. Extracellular microcystins within irrigation water may leach into soils from constant spray, increasing the bioavailability of toxin [ 48 ]. Two studies indicated that contaminated irrigation water with microcystins threaten crop quality and yield.…”
Section: Input Pathwaysmentioning
confidence: 99%
“…Irrigation with polluted water is the primary route of introduction of cyanotoxins (microcystins) in agricultural soils. Extracellular microcystins within irrigation water may leach into soils from constant spray, increasing the bioavailability of toxin [ 48 ]. Two studies indicated that contaminated irrigation water with microcystins threaten crop quality and yield.…”
Section: Input Pathwaysmentioning
confidence: 99%
“…It is hypothesized that ALS patients in this region cannot prevent BMAA accumulation [ 36 , 37 , 38 ]. The dietary source of BMAA could be seafood such as fish, mussels, crabs, and oysters [ 39 , 40 , 41 ]. High incidence of ALS has also been reported on the island of Guam whose population use potential cycad-derived products.…”
Section: Discussionmentioning
confidence: 99%
“…However, after 3 weeks, the alfalfa plants are still considered seedlings, and even though most of the MC-LR taken up from the 2.1 soil remained in the roots, the toxin could be transported to the shoots as the plants grow. Differences in cyanotoxin uptake and distribution within the plant appendages were previously shown (Esterhuizen-Londt and Pflugmacher 2019). Therefore, it is likely that at the seedling growth stage, nutrients essential for growth are prioritised for transport from nutrient-poor soil such as the 2.1 soil type to support growth.…”
Section: Plant Exposurementioning
confidence: 94%